Can-Can [videorecording (DVD)] - Lang, Walter, 1898-1972; Sinatra, Frank, 1915-1998; MacLaine, Shirley, 1934-; Chevalier, Maurice, 1888-1972; Jourdan, Louis; Prowse, Juliet, 1936-1996; Dalio, Marcel, 1900-1983; Porter, Cole, 1891-1964; Burrows, Abe, 1910-1985 (20th Century Fox Home Entertainment, 2007)
The owner of Montmartre's most notorious nightspot, the Café Le Bal Du Paradis, Simone Pistache spends a great deal of her time in court, thanks to the banning of that "lewd and lascivious" dance, the Can-Can. So when her nightlife-loving lawyer and boyfriend, François Durnais, refuses to settle down and marry her, Simone decides to play up to his rival in romance, Parisian judge Philipe Forrestier, a lovestruck young jurist who's determined to make an honest woman out of her-- one way or the other.